Polymeric pullulan films incorporated with extract of Cyclospermum leptophyllum (pers.) Sprague for healing purposes (Research, Society and Development, 2022)
Healing films provide excellent results in the adjuvant treatment of injuries. Its association with plant extracts allows the achievement of therapeutic activities, favoring skin regeneration. This study aimed to develop pullulan films incorporated with an extract from the aerial parts of Cyclospermum leptophyllum to be used as healing dressings and to evaluate their morphological and physicochemical characteristics and their potential antioxidant activity. Polymeric films in the proportion of 4% PU (m/v) and 15% plant extract and control films composed only of the polymer matrix were produced using the casting method. The films were evaluated for thickness, visual aspects, solubility, water vapor permeability, swelling, degradation, and antioxidant activity. They showed good appearance and flexibility but heterogeneity due to the precipitation of components. A high degree of solubility and swelling was observed, and despite its rapid dissolution in contact with water, the formation of a hydrogel can enable greater adherence to wounds. The films have controlled water vapor transmission, that allows gas exchange. A DPPH radical inhibition rate of 17.23% was obtained, proving its antioxidant activity. Therefore, the biofilms produced have healing potential, which can be better studied in the future through tests demonstrating antimicrobial, and anti-inflammatory activities.